Simulation of Overlap Effect on Savonius Wind Turbine Performance by Varying Cylinder Distance in Front of Returning Blade - Projek Priyonggo Sumangun Lukitadi; Priyo Agus Setiawan; Fariz Andika Firmansyah (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2023)
The performance of Savonius wind turbine was improved in the previous experimental studies that added overlap and variation of disruptive cylinder distances in front of returning blade. However, the study could not display flow visualization such as velocity contours, streamlined velocity, and pressure contours on turbines so further research is needed. This research is in the form of numerical study using 3-dimensional Computational Fluid Dynamics (CFD) method. The simulation is, determine visualize the turbine’s flow like a velocity contours, streamlined velocity, and pressure contours. The turbine has the same diameter and height of 0.4 meters with overlap addition. The various distances of the disruptive cylinder used is S/d = 1.4; S/d = 1.7 ; S/d = 2 and S/d = 2.3. The final result shows that the visualization at a distance of S/d = 1.7 is the most optimal wake distance to cover the overall returning blade side so that the performance of the Savonius wind turbine at that distance is highest compared to other variations.